KEPEMIMPINAN PENDIDIKAN DALAM MANAJEMEN KOPERASI SEKOLAH - Alip Fikri Abdillah; Aziz Musafah; Hani Agustin Nugroho; Siswadi (STKIP Subang, 2026)
This study aims to analyze the role of educational leadership in the management of school cooperatives and to identify the challenges faced in their implementation. School cooperatives have a strategic function as a medium for entrepreneurship learning and the development of students’ character. However, their success is highly influenced by the quality of educational leadership, particularly that of school principals and supervising teachers. This study employs a library research method, which involves reviewing and analyzing various sources of literature such as books, academic journals, and relevant research findings. The results indicate that educational leadership plays roles as planner, organizer, motivator, supervisor, decision maker, human resource developer, and liaison with stakeholders. Effective leadership is able to enhance student participation, build a positive organizational culture, and optimize the function of cooperatives as a learning medium. Nevertheless, several challenges remain, including limited managerial competence, low student participation, limited resources, lack of technology utilization, and weak coordination. Therefore, innovative, collaborative, and transformational leadership is needed to ensure that school cooperatives can develop optimally and sustainably.